Rule-making, rule-breaking?: law breaking by government in the Netherlands and the United Kingdom - Huberts, Leo W. (Crime, law and social change, 2006)
This article concerns a relatively novel issue: rule breaking and unlawful conduct by government bodies; to which degree does it occur, what is the nature of this misconduct, what are the underlying motives, and what are the consequences and possible solutions? Rule and law breaking is harmful for the credibility and integrity of a state and its law enforcement system. However, very little empirical research has been carried out into this issue, in comparison to research into state crime. There is little clarity about how public actors deal with criminal and administrative laws and rules in areas like environmental protection, safety regulations and working conditions. Do government bodies set a good example? Is their behaviour better or worse than the public and businesses? An analytical framework for research will be presented and also the results of an extensive research project in the Netherlands; the main themes of which have been benchmarked against data from the United Kingdom. The article will conclude with a summary of the main findings and a number of suggestions for further research and policy development.